1992
DOI: 10.3168/jds.s0022-0302(92)77947-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Late Gestation Heat Stress on Postpartum Milk Production and Reproduction in Dairy Cattle

Abstract: Carry-over effects of late gestation heat stress on postpartum productive and reproductive traits were estimated from DHI records using 341 lactations from six sites in Mississippi. Climatological data were gathered from records of weather stations near the sites. Using multiple linear regression analyses, predictor variables for lactations were age at calving, lactation number, maximum degree-days (above 32.2 degrees C) during the periods 30 and 60 d prepartum, and precipitation 30 and 60 d prepartum. Months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 12 publications
1
10
0
2
Order By: Relevance
“…Lewis et al (1984) observed smaller corpus lutea after parturition, and greater concentrations of 13, 14-dihydro-15-keto-prostaglandin F 2 in nonshaded cows than in shaded cows during the last third of gestation. The authors speculated that corpus Moore et al (1992) computed maximum degree days at 30 and 60 d prepartum. They reported no significant effect of these heat stress measurements on DOP or SPC or the subsequent lactation.…”
Section: Climatic Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis et al (1984) observed smaller corpus lutea after parturition, and greater concentrations of 13, 14-dihydro-15-keto-prostaglandin F 2 in nonshaded cows than in shaded cows during the last third of gestation. The authors speculated that corpus Moore et al (1992) computed maximum degree days at 30 and 60 d prepartum. They reported no significant effect of these heat stress measurements on DOP or SPC or the subsequent lactation.…”
Section: Climatic Variablesmentioning
confidence: 99%
“…However, days to first estrus, days open and services per conception were not different between these groups of cows. Moore et al (1992) investigated the carry-over effects of heat stress during late gestation period on some postpartum reproductive parameters using maximum prepartum degree-days (MPDD). They could not detect a relationship between MPDD at 30 or 60 d with days open or services per conception.…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al (1992) reported that maximum degree-days 60 days before calving, which were the cumulative number of degrees that the maximum temperature was above 32.2°C during the dry period, negatively affected milk and milk fat production of Holstein cows during their first 100 days of lactation. Collier et al (1982b) reported that dairy cows exposed to hot conditions during late gestation had calves with lower birth weights, and produced less milk than cows not exposed to hot conditions.…”
Section: Introductionmentioning
confidence: 98%
“…However, temperature-dependent maternal effects can also play a role, through effects on milk production and behaviour of the mothers. It is commonly known that elevated body temperatures and heat stress in livestock animals cause distress and lead to an increased respiration rate, reduced activity and food intake and furthermore to negative effects on breeding performance by reducing fertility [15, 16]. Conceivably, high ambient temperatures have adverse effects on milk production in species such as laboratory mice ( Mus musculus ) [17], common voles ( Microtus arvalis ) [18], Brandt’s voles ( Lasiopodomys brandtii ) [19], Mongolian gerbils ( Meriones unguiculatus ) [20] but also in dairy cattle ( Bos taurus ) [2124].…”
Section: Introductionmentioning
confidence: 99%